Resursutvärdering av insatsmöjligheter : Huvudkulvertsystem vid SSAB EMEA, Luleå - Bergman, Joakim (2013)
SSAB EMEA is one of the world's most prominent industries in the steel manufacturing. In order to ensure continuous production of steel and an otherwise functioning operation some vital features must work. One of those vital features that affect all functions within the organization is the distribution of electrical energy. Below ground at SSAB EMEAs area there are cable culverts where power supply and control cables are located. Power supply cables provides processes and facilities in the area and control cable for controlling the manufacturing process.A fire in any part of these cable culverts would cause serious consequences from an economic perspective and may also result in serious injury or death.The work of this report has examined what SSAB EMEAs own organization can do in a fire incident in the cable culvert. It was necessary to find out what the internal emergency service could do in case of a fire incident. The division of electrical distribution at SSAB EMEA also has an important role in case of a fire incident because of their expert skills regarding electrical equipment.Four main issues were identified and became the basis for the further work.• Culvert design and its fire protection?• The proactive safety works in the organization in terms of material and education?• What is the knowledge in terms of safety behaviour in spaces with electrical installations of the staff at the internal fire department?• What procedures are there for the staff of electrical distribution to make the cables current less in a fire scenario?The methods used to make this resource assessment of the organization are largely based on site visits and interviews at both the department for distribution and on the internal emergency service.Initially it was considered important to get better insight in the two different departments. What resources had each department? What was their view of the issue and its problems? Several visits to the culvert system was carried out to see what physical conditions the facility was in terms ...